Undergraduate students’ perceptions toward Google Classroom integration into EFL classroom: a sequential explanatory study at an Indonesian university - Lutfin Nurbuat; Moh. Arif Mahbub; Ifan Andri Firdaus (Journal on English as a Foreign Language, 2022)
Many academic works of literature have acknowledged Google Classroom (henceforth, GC) in assisting pedagogical practices, particularly for virtual classroom instructions. Yet, there has been limited research about GC investigating participants' views about GC-mediated instructions in an EFL setting. This study investigated Indonesian undergraduate students' perceptions of GC integration in the EFL context. This sequential explanatory mixed-methods aimed to investigate the undergraduate students' views about GC utilization in the EFL domain. Six participants from a private university in Jember, Indonesia, were voluntarily involved in this study. Data were collected through a web-based questionnaire and a series of semi-structured interviews to get in-depth information with respect to their opinions related to GC integration in such a context. The findings report that GC has been recognized for its ease of use, being easily accessible, promoting teacher-student interactions, and creating a more interactive online learning atmosphere. The study concluded with the proposition that the majority of participants were affirmative in accepting GC in their virtual classroom. The analysis also revealed implications for both EFL teachers and students. Limitations and recommendations were then provided.